Patients' views on asthma-specific quality of life questionnaires: qualitative interview study in Germany - Apfelbacher, Christian; Weiß, Melanie; Saur, Joachim; Loerbroks, Adrian (Journal of asthma, 2012)
OBJECTIVE: It is unclear which of the commonly used asthma-specific quality of life (QoL) questionnaires best capture the lived experience of people with asthma. The objective of this study was to explore patients' views on three asthma-specific QoL questionnaires. METHODS: Ten adult individuals with asthma were asked to complete three asthma-specific QoL questionnaires (Standardized Juniper Asthma Quality of Life Questionnaire (AQLQ-J-s), Sydney Asthma Quality of Life Questionnaire (AQLQ-S), and Fragebogen zur Lebensqualität bei Asthma (FLA)). Interviews were conducted to elicit patients' views on the questionnaires. Interviews were transcribed verbatim and thematic content analysis was performed. RESULTS: Participants spoke about response format and options, missing and redundant/similar content as well as content that was perceived to be irrelevant. A lack of specificity was named for some items, and issues concerning layout were raised. Despite the diversity of views expressed, participants mostly agreed on the ranking of the questionnaires and, overall, favored the AQLQ-S. CONCLUSIONS: Patient involvement highlights shortcomings and strengths of various asthma-specific questionnaires in terms of both format and content. The AQLQ-S was the most positively perceived questionnaire. Future research will need to explore other settings and potentially involve a larger and more diverse sample.
Gesehen am 02.07.2018